2021
DOI: 10.1038/s41598-021-95774-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between intervertebral oblique lumbar interbody fusion and transforaminal lumbar interbody fusion: a multicenter study

Abstract: This study aimed to perform a comparative analysis of postoperative results between lumbar degenerative spondylolisthesis (LDS) treated with oblique lateral interbody fusion (OLIF) and transforaminal lumbar interbody fusion (TLIF) from the Chiba spine surgery registry database. Sixty-five patients who underwent single-level OLIF (O group) for LDS with ≥ 3 years’ follow-up were retrospectively reviewed. The control group comprised 78 patients who underwent single-level TLIF (T group). The analyzed variables inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
(26 reference statements)
3
22
1
Order By: Relevance
“…In the same study, pooled analyses identified no significant differences in the overall complication rate and complication types [ 68 ]. Other comparative studies also reported similar complication rates between the surgical methods [ 66 , 67 , 69 ].…”
Section: Clinical and Radiological Outcomes Of Olifsupporting
confidence: 53%
See 1 more Smart Citation
“…In the same study, pooled analyses identified no significant differences in the overall complication rate and complication types [ 68 ]. Other comparative studies also reported similar complication rates between the surgical methods [ 66 , 67 , 69 ].…”
Section: Clinical and Radiological Outcomes Of Olifsupporting
confidence: 53%
“…The authors found that the improvement in the psychological domain in the Japanese Orthopedic Association Back Pain Evaluation Questionnaire (JOABPEQ) was more significant in patients who underwent OLIF. However, Takaoka et al [ 67 ] reported that there were no significant differences in clinical scores, including VAS and JOABPEQ scores, between the 2 surgical methods in their retrospective multicenter study.…”
Section: Clinical and Radiological Outcomes Of Olifmentioning
confidence: 99%
“…Oblique lumbar interbody fusion (OLIF) is an effective treatment for patients with degenerative lumbar disc disease. Indirect decompression of neural elements can be achieved by distracting the reduced intervertebral space with an enlarged interbody cage, thus alleviating neurogenic intermittent claudication [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 Several comparative studies have examined various LIF techniques, focusing on local radiographic characteristics, fusion rates, and clinical outcomes to provide a comparison. 1,2,4,7,9,10,13,23,25 However, most studies have only conducted one-to-one comparisons between two surgical techniques. Moreover, although multilevel LIF has been shown to impact global sagittal alignment and even result in an iatrogenic flatback, studies evaluating global sagittal alignment after LIF are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although multilevel LIF has been shown to impact global sagittal alignment and even result in an iatrogenic flatback, studies evaluating global sagittal alignment after LIF are scarce. 1,6,13,16,23 This study evaluated the surgical outcomes of various LIF approaches (ALIF, OLIF, and TLIF) for lumbar degenerative disorders. We compared the outcomes between the different treatment groups, with special consideration for spinopelvic parameters, to assess the impact of each approach on changes in global sagittal alignment.…”
Section: Introductionmentioning
confidence: 99%